Faktor Faktor Yang Berhubungan Dengan Pemanfaatan Layanan Antenatal Care (Anc) Terpadu Pada Ibu Hamil Di Puskesmas Putri Ayu Kota Jambi Tahun 2025 - Muthia Chairunnisa; Asparian; Arnild Augina Mekarisce; Dwi Noerjoedianto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Maternal Mortality Rate (MMR) remains a major public health concern in Indonesia. Optimal utilization of Antenatal Care (ANC) is essential for early detection of pregnancy-related risks and prevention of maternal complications. Maternal knowledge, family support, and the quality of healthcare services may influence ANC utilization. This case-control study analyzed the association of maternal knowledge, family support, and healthcare service quality with ANC utilization among 60 respondents (30 cases and 30 controls) at Putri Ayu Public Health Center, Jambi City. Data were collected using structured questionnaires and analyzed with the Exact McNemar test at a 95% confidence level. Results: Maternal knowledge was significantly associated with ANC utilization (p = 0.039). However, family support (p = 0.727) and healthcare service quality (p = 0.250) showed no significant association. Maternal knowledge significantly influences ANC utilization, whereas family support and healthcare service quality do no